A mathematical model of HIF-1 regulated cellular energy metabolism - Bocharov, Gennady; Jäger, Willi; Knoch, Jonas; Neuss-Radu, Maria; Thiel, Manfred (Vietnam journal of mathematics, 2021)
In this study, we formulated a mathematical model of hypoxia-inducible factor 1 (HIF-1) mediated regulation of cellular energy metabolism describing the reprogramming of cell metabolic processes from oxidative phosphorylation to glycolysis under reduced oxygen levels. The model considers the dynamics of fifteen biochemical species and the proton concentration with the underlying reaction processes localized in three intracellular compartments, i.e. the cytoplasm, mitochondrion and nucleus. More than sixty parameters of the model were calibrated using both the published data and the system steady-state based identification procedure. The model was validated by generating predictions which could be compared to empirical observations. The model behaviors representing the cell metabolism switching over in response to transitioning from a normoxic to hypoxic environment are consistent with the current views of the role of HIF-1 in hypoxia.